Simple method to determine the resolution and sensitivity of systems for optoacoustic tomography - González, Martín Germán (2018)
In this paper we present a method to determine the spatial resolution and sensitivity of systems for optoacoustic tomography (OAT). The method consists of obtaining the image of a sample based on a transparent film embedded in agarose. The film has a certain pattern made with a laser printer that allows to obtain the system spatial resolution. Moreover, since the damage threshold of the ink pattern is similar to that of living tissue, it is also possible to determine if the system is sensitive enough to be applied on biological samples. The method is straightforward, fast and repeatable, and was tested in a OAT system for obtaining two-dimensional images developed in our laboratory.